PENINGKATAN DISIPLIN KERJA GURU MELALUI PERAN KEPALA SEKOLAH DI SD NEGERI 30 MANDAU - Asniwati Asniwati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
Qualified teachers have a high work ethic and excellent work discipline. Work discipline is an attitude, action, and behavior according to the rules to obey all school rules based on the teacher's self-awareness. Facts in the field there are still teachers who ignore work discipline, such as teachers who are too late to come to school, teachers dress neatly, there are still teachers who have not prepared a teaching program before presenting material in front of the class, thus adversely affecting the learning process. The purpose of this research is to improve teacher work discipline through the role of the principal in SD 30 Mandau. The subjects of this study were all teachers in SD 30 Mandau, totaling 18 people. This type of research is the School Action Research. The research process consists of two cycles, namely cycle I and cycle II, each cycle consisting of several stages, such as: 1) Planning; 2) Implementation; 3) Observations; and 4) Reflection. The results showed, in the first cycle, seen from the presence of teachers, from 18 teachers the average value of teachers was 72.4 after the second cycle increased to 94.5, an increase of 22.1%. Judging from the neatness of the teacher got an average value of 69.1, in the second cycle increased to 90.3 increased by 21.2%. Judging from the neatness the teacher got an average value of 60.8, in cycle II it increased to 91.0, an increase of 30.2%. Judging from the completeness of the administration the teacher gets an average value of 65.9, in the second cycle increased to 81.9, an increase of 16%, and seen from the process of implementing the learning of the teacher gets an average value of 68.4, in the second cycle increases to 91.4 increased by 23%. Can the researchers conclude that through the role of the principal can improve the work discipline of teachers in SD Negeri 30 Mandau